IMPLEMENTASI PROGRAM FASILITASI DAN STIMULASI PEMBANGUNAN PERUMAHAN MASYARAKAT KURANG MAMPU DI KECAMATAN PADANG HILIR KOTA TEBING TINGGI PROVINSI SUMATERA UTARA - Ridho Afandi; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The implementation of program facilitation and stimulation the construction of housing among the less well-off is rehabilitation program to the roof, the floor and the walls of held by Tebing Tinggi city regional government given to low income people the effect on greater the condition of the poor. The purpose of this research to review and analyze The Implementation Of Program Facilitation And Stimulation The Construction Of Housing Among The Less Well-Off In Padang Hilir Sub District Tebing Tinggi City North Sumatra Province. The concept of the theory used is communication, resources, disposition and bureaucracy structure. Researcher used the theory George C.Edwards III. Researcher from is provided by way of qualitative research was conducted. Collecting data used the technique of observation, interviews and documentation. Informants chosen using a technique purpose of sampling the sample decided not randomly. The results of this research program has been done our best but in the implementation stage did not go entirely according to plan there is still going on a problem associated with factors obstacles in the field on a time of inaccurate, labor implementation and inaccurate development goals. Keywords : Implementation,  Construction,  Among The Less Well-Off